Psychometric Characteristics of the Positive Leadership Scale in the Palestinian Environment - Obedat , Fatmeh Ali; Jondi, Nabil (Dirasat: Educational Sciences, 2024)
Objectives: This study aims to extract the psychometric characteristics of the Positive Leadership Assessment Scale (PLAS) and identify its factor structure, as well as to validate it in the Palestinian context. Methods: The descriptive approach was adopted through exploratory and confirmatory factor analysis, and it was possible to verify the construct validity by calculating the item-total correlation coefficient. In addition, the reliability was assessed using Cronbach’s alpha and test-retest reliability. A non-homogeneous stratified sample of (312) male and female principals was selected from the principals of schools in the West Bank, Gaza Strip, the occupied territories, and Jerusalem in Palestine, at the beginning of the second semester of the academic year (2022-2023). Results: The confirmatory factor analysis, following the Varimax rotation method, resulted in four factors (dimensions) that the scale saturated: First, in the foremost position, was the factor of Positive Communication. Second, in the second position, was the factor of Providing Positive Meanings. Third, in the third position, was the factor of Positive Climate and Relationships. Finally, in the fourth and last position, was the factor of Positive Strategies. Conclusions: Having the standardized scale possessing psychometric properties enables its utilization in future studies.